Interspecific competition between egg parasitoids: native Fopius caudatus and exotic Fopius arisanus, in Ceratitis cosyra - Karlsson, M.F.; Souza, E.O. de; Ayelo, P.M.; Zannou, J.A.; Mègnigbèto, G.S.B.; Bokonon-Ganta, A.H. (Elsevier, 2018)
Tephritidae fruit flies are parasitized by Braconidae wasps, of which some are used in biological control programs. Releases of exotic parasitoids might affect, or be affected by, native species exploiting a common host. We studied interspecific competition between the native African parasitoid Fopius caudatus (Szépligeti) and the exotic Asian parasitoid Fopius arisanus (Sonan) (both Hymenoptera: Braconidae) in African native Ceratitis cosyra Walker (Diptera: Tephritidae). Wasp behaviour on infested fruits and dissection of fruit fly eggs assessed acceptance, oviposition performance and suitability for egg development, parasitism, and effect of parasitism by heterospecific species. While F. arisanus outcompeted F. caudatus in parasitization of relatively younger eggs, chased away F. caudatus, and oviposited more, F. caudatus survived better than F. arisanus. Fopius caudatus parasitized more in 2-day-old C. cosyra eggs than in 1 or 3-day-old egg. More oviposition by F. caudatus was found in fruits previously exposed to F. arisanus, coinciding with presence of more developed host eggs, while such difference was not observed for F. arisanus. Fopius caudatus was an inferior competitor than F. arisanus in C. cosyra-infested African mango Irvingia gabonensis (Irvingiaceae).